Effects of life-place trajectories based on municipality of residence on old-age mortality: evidence from sequence analysis in 20th century Netherlands - Dolores Sesma Carlos; Jan Kok; Michel Oris (Espace populations sociétés)
Research has shown that the place of residence may affect health and wellbeing but there has been little attention on whether long life-place trajectories based on municipality of residence are associated with old-age mortality. By applying a "life course of place" approach to health in later life, our aims are to examine (a) what patterns in individuals’ life-place trajectories during the first fifty years of life were identified in terms of proximity to social support in the place of origin and residential context, (b) how old-age mortality was associated with these life-place trajectory patterns, and the extent to which early, adult and later-life factors mediated these associations, and (c) how these associations varied by marital status and through time. We used geocoded longitudinal data for all municipalities of residence in the Netherlands in a subsample of 20,359 persons (≥50 years old, 50% women) of Dutch cohorts, born between 1850 and 1922. Cluster Analysis was first applied to describe life-place trajectory patterns based on residential geographic proximity and residential context for each year of life from birth until age fifty. Cox proportional hazard regression models were performed in a second step to estimate the associations between life-place trajectories and old-age mortality. They were first adjusted for gender, age and cohorts, then adjustment for early-life, adult and old-age factors were added. Interaction terms were applied to investigate the moderating effect of marital status and cohorts. Results showed that (a) after adjustment, life-place trajectories of moderate-long distance from birthplace had a significant association with higher risk of mortality in old age; (b) adult and elderly factors mediated the influence of these patterns on old age mortality; (c) marital status and birth cohorts moderated the associations. The conjoined effect of trajectories characterized by long distance from place of origin and widowhood, suggested a combination of two proxy measures of weak social relationships with detrimental consequences in later life. Conclusions: This study suggested mechanisms linking life-place trajectories according to municipality of residence to old-age mortality. Results highlighted the possible role of migrations’ histories, combined with marital status and changes over time, in survival at old-age.